PERBANDINGAN KINERJA KEUANGAN PEMERINTAH PROPINSI DI INDONESIA - Fadhilah Nuraini; Kiagus Andi; Yunia Amelia; Fitra Dharma (Jurnal Akuntansi dan Keuangan (JAK), 2019)
The purpose of this study is to compare the financial performance of the provincial governments in Java and Sumatra in the 2014-2017 period and to determine the differences in the financial performance of the provincial governments in Java and Sumatra in the 2014- 2017 period.The research method used is quantitative research methods. The population in this study is the report of the Realization of Regional Government Revenue and Expenditures of Provincial Governments in Indonesia in 2014-2017. The sample selection uses a purposive sampling technique that is sampling taking into account certain characteristics and criteria.The results of this study are based on the results of descriptive analysis in mind that the financial performance of provinces in Java is better than provinces in Sumatra. While the results of different tests show that there is no significant difference in the financial performance of the provincial governments in Java and Sumatra because it shows a significance value of more than 0.05.